EXPLORING THE PARAPHRASING SKILLS OF ENGLISH STUDENTS AT THE UNIVERSITY OF SERAMBI MEKKAH BANDA ACEH: AN INSIGHT INTO ACADEMIC PROFICIENCY - Riska Amelia; Faudi Faudi; Muchsin Muchsin; Cut Faizah (UNIVERSITAS SERAMBI MEKKAH, 2024)
Paraphrasing is the ability to restate an idea or phrase in a new form without changing its original meaning. This skill is particularly important in academic writing, where plagiarism is a common problem, especially in dissertations and scientific papers. The purpose of this research was to investigate the paraphrasing skills of English students at Serambi Mekkah University, Banda Aceh, and to identify the challenges they face in mastering this skill. Using a quantitative research approach, the study collected data by asking students to paraphrase sentences from essays that reflect the writer's perspective on certain topics. These essays were distributed via Google Forms to students on the English Education programme. The results showed a range of paraphrasing abilities among the students: 33% were excellent, 20% were good and 15% were fair. Conversely, 20% of the students had poor paraphrasing skills and 12% had significant difficulties. These findings highlight that paraphrasing is an essential academic skill, crucial for avoiding plagiarism and improving the quality of writing. The research underlines the importance of teaching students effective paraphrasing techniques to enable them to produce original work and adhere to ethical writing practices. It also provides valuable insights for educators, suggesting that targeted instruction in paraphrasing could help students improve their writing and reduce the risk of academic misconduct. By mastering paraphrasing, students can not only improve their academic performance, but also develop the critical thinking and language skills necessary for effective communication.